Aplikasi Surfaktan Alami dan Sintetis untuk Meningkatkan Penghilangan Total Petroleum Hidrokarbon dari Tanah Tercemar - Esti Dyah Arum Mawarni; Bieby Voijant Tangahu; Ary Bachtiar Khrisna Putra (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Environmental pollution by petroleum hydrocarbons (total petroleum hydrocarbons) is an environmental problem affecting human health and the environment. Innovative and sustainable treatment methods are needed to solve this problem. One remediation technique that can be used is soil washing. Soil washing is a remediation technique using surfactants as a contaminant washing solution. This research study investigated the washing of soil contaminated by used motor oil using green and synthetic surfactants. The type of natural surfactant used was saponin at a concentration of 10,000 mg/L and synthetic surfactant Linear Alkylbenzene Sulfonate (LAS) at 800 mg/L. The effect of washing time and stirring speed on TPH reduction efficiency was also tested through a series of laboratory tests. Based on the statistical results, the three factors, namely surfactant type, washing time, and stirring speed, significantly influenced TPH removal. Optimum removal efficiency with LAS surfactant was obtained under washing time between 70 -90 minutes and stirring speed between 40 -50 rpm. Meanwhile, saponin surfactant at washing time is 60 -80 minutes, and stirring speed is 48 -50 rpm.